PENGARUH MEDIA PEMBELAJARAN KOLABORATIF TERHADAP PENINGKATAN LITERASI DIGITAL DAN KREATIVITAS SANTRIWATI DI PONDOK PESANTREN PUTRI KH. AHMAD BASTOMI - Nicky Dwi Kurnia (Educational Technology Journal, 2025)
This study examines the effectiveness of collaborative learning media in enhancing digital literacy and creativity among female students at Pondok Pesantren KH. Ahmad Bastomi Mojosari Loceret. The study subjects consisted of 50 female students. The research design was a quasi-experiment (one-group pretest–posttest) with data collection methods including digital literacy tests, creativity questionnaires, observations, and interviews. The results showed an increase in average digital literacy scores from 65% (pre) to 80% (post). Statistical analysis (paired t-test) indicated a significant difference (t ≈ 7.07; p < 0.001). Furthermore, 75% of respondents showed an increase in creativity according to questionnaires and observations; a proportion test against the random proportion of 50% yielded z ≈ 3.535 (p ≈ 0.0004). Implications: The application of adaptive collaborative media can be an effective strategy to address the limitations of mobile phone access in boarding schools and improve information exploration skills as well as the creativity of female students.